Implementation of Electronic Customer Relationship (e-CRM) in Increasing Customer Loyalty PT Cromwell Indonesia - Sinulingga, Herdiyana Br; Digdowiseiso , Kumba (CV ODIS, 2024)
The need for clean water and the decreasing availability of clean water are the driving factors for water treatment business players. Every company competes to provide the best service to increase customer loyalty. The method used to increase customer loyalty is customer relationship management (CRM). This research explains the implementation of e-CRM in increasing customer loyalty at PT Cromwell Indonesia. This research uses a descriptive qualitative approach. The primary data source is data obtained from interviews and direct observation at the head office of PT Cromwell Indonesia. From the research results, PT Cromwell Indonesia has implemented e-CRM by using various media such as social media, WhatsApp, e-mail, and an e-CRM software Qontak.